Research Progress of Cholestatic Liver Disease-Related Pruritus in Chinese Medicine and Western Medicine - Dai, Wenzhang; Nie, Hong (Chinese medicine and natural products, 2024)
Pruritus is common in cholestatic liver disease, with a high clinical incidence rate and complex pathogenesis. Accumulation of potential pruritus inducers such as steroids, bile acids, and lysophosphatidic acid in the systemic circulation is the main cause of pruritus in cholestatic liver disease. Currently, clinical treatment of cholestatic liver disease-related pruritus mainly includes medication, intervention therapy, and some experimental methods. However, there are still problems, such as unclear pathological mechanisms and unsatisfactory treatment responses in some patients with cholestatic liver disease-related pruritus. Effective treatment for patients still faces challenges. By extensively screening patients' plasma (and/or bile) samples through clinical trials, potential pruritus inducers can be identified comprehensively, which can provide a deeper understanding of the itch signaling pathways in cholestatic liver disease and a basis for the development of treatment strategies. Traditional Chinese medicine (TCM) has shown certain characteristics and advantages in clinical treatment. Based on the etiology and pathogenesis, external application, internal administration, and TCM-specific therapies have achieved good clinical efficacy. Similarly, the combination of Chinese medicine and Western medicine has also achieved more effective treatment for patients with cholestatic liver disease-related pruritus. This article will introduce the latest progress in the study of pruritus inducers in cholestatic liver disease and its treatment in TCM and Western medicine.
Keywords: cholestasis; pruritus; Chinese medicine; Western medicine; research progress